Pemikiran Nursamad Kamba tentang Formulasi Tauhid - Ahmad Hudatullah; Bambang Qomaruzzaman; Yumna Yumna (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
Tawhid according to the Sufis is different from the meaning of the Theologians. The purpose of this study is to discuss tawhid in Nursamad Kamba's thinking and the mechanisms for achieving it. This research methodology uses qualitative using literature research. The results of this study show that in Nursamad Kamba's view tauhid is an experience of manliness or mortal', mortal can be obtained through the makrifat mechanism which is divided into two ta'aruf and ta'rif. Tawhid is the result of the integration of three potentials in the human mind, namely intellectual, psychic and spiritual, so there needs to be further study of the sufistic psychoanalysis of Nursamad Kamba's perspective.